An Approximation to What Language Immersion Programs are Like - Ayala Zárate, Jair (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this article, I present the results from an analysis that looked at relevant studies in relation to language immersion programs (and similar ones), as well as their implementation in various contexts. First, I will show how the concept of immersion has evolved and been shaped and re-shaped through time and different geo-political positions. Second, I will problematize language immersion programs and their implementation based on a decolonial perspective.